2004
DOI: 10.1037/0012-1649.40.6.1059
|View full text |Cite
|
Sign up to set email alerts
|

More gestures than answers: Children learning about balance.

Abstract: This research extends the range of domains within which children's gestures are found to play an important role in learning. The study involves children learning about balance, and the authors locate children's gestures within a relevant model of cognitive development-the representational redescription model (A. Karmiloff-Smith, 1992). The speech and gestures of children explaining a balance task were examined. Approximately one third of the children expressed one idea in speech and another in gesture. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 34 publications
5
112
1
1
Order By: Relevance
“…Even blind individuals who have never seen gesture move their hands as they talk (Iverson & Goldin-Meadow, 1998). Moreover, the gestures learners produce when explaining a task predict whether they will soon master that task (Church & Goldin-Meadow, 1986;Perry, Church, & Goldin-Meadow, 1988;Pine, Lufkin, & Messer, 2004), and learners who gesture spontaneously on a task are more likely to retain what they have learned about the task than learners who do not gesture (Alibali & Goldin-Meadow, 1993;Cook & Goldin-Meadow, 2006). These findings suggest that gesturing can promote learning.…”
mentioning
confidence: 56%
“…Even blind individuals who have never seen gesture move their hands as they talk (Iverson & Goldin-Meadow, 1998). Moreover, the gestures learners produce when explaining a task predict whether they will soon master that task (Church & Goldin-Meadow, 1986;Perry, Church, & Goldin-Meadow, 1988;Pine, Lufkin, & Messer, 2004), and learners who gesture spontaneously on a task are more likely to retain what they have learned about the task than learners who do not gesture (Alibali & Goldin-Meadow, 1993;Cook & Goldin-Meadow, 2006). These findings suggest that gesturing can promote learning.…”
mentioning
confidence: 56%
“…For example, gesture may be used to explore when novel conceptualizations are useful (Kita, 2000)-and gestures that manifest this exploration are most frequent when conceptual exploration is useful. In support of this claim, several studies have shown that children produce gesture-speech mismatches most frequently when they are at the cusp of understanding a task (Church & Goldin-Meadow, 1986;Perry et al, 1988;Pine et al, 2004).…”
Section: Relationship Among the Four Functionsmentioning
confidence: 96%
“…Variability also features in the microgenetic approach. This focus on variability is shown, among others, in the work of Siegler (1994Siegler ( , 1996Siegler ( , 1997, Goldin-Meadow, Alibali, and Church (1993), Alibali (1999), Granott (1993), Granott (1995), Fischer, Bullock, Rotenberg, andRaya (1993), Fischer and Yan (2002), Lautrey, Bonthoux, and Pacteau (1996), Lautrey (1993), Lautrey and Cibois (1994), Tunteler and Resing, (2002), Granott (1998Granott ( , 2002, Pine, Lufkin, and Messer (2004) and Flynn, O'Malley, and Wood (2004).…”
Section: Variabilitymentioning
confidence: 99%